2009
DOI: 10.1007/s11908-009-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of human and animal bite wound infection: An overview

Abstract: Animal and human bite wounds can lead to serious infections. The organisms recovered generally originate from the biter's oral cavity and the victim's skin flora. Anaerobes were isolated from more than two thirds of human and animal bite infections. Streptococcus pyogenes is often recovered in human bites, Pasteurella multocida in animal bites, Eikenella corrodens in animal and human, Capnocytophaga spp, Neisseria weaveri, Weeksella zoohelcum, Neisseria canis, Staphylococcus intermedius, nonoxidizer-1, and eug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 55 publications
1
31
0
3
Order By: Relevance
“…Bacteria involved in wound infections after crocodilian attacks include Aeromonas hydrophila, Burkholderia pseudomallei, Pseudomonas spp., Serratia spp., Citrobacter diversus, Enterococcus spp., Clostridium spp. and Pantoea agglomerans (Raynor et al 1983, Flandry et al 1989, Mekisic & Wardill 1992 (Murphey et al 1992, Blaylock 1999, Goldstein et al 2002, Kunimoto et al 2004, Jofré Morales et al 2006, Brook 2009.In the present study we found 24 reported cases of attacks by crocodiles on humans in the Yucatan Peninsula, most of them (87.5%) occurring in Quintana Roo and in the city of Cancun, which are the state and city in the peninsula, respectively, most frequented by tourists. Both crocodile species (Crocodylus acutus and C. moreletii) were involved in the attacks and C. moreletii was involved in 2 cases of fatal attacks.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Bacteria involved in wound infections after crocodilian attacks include Aeromonas hydrophila, Burkholderia pseudomallei, Pseudomonas spp., Serratia spp., Citrobacter diversus, Enterococcus spp., Clostridium spp. and Pantoea agglomerans (Raynor et al 1983, Flandry et al 1989, Mekisic & Wardill 1992 (Murphey et al 1992, Blaylock 1999, Goldstein et al 2002, Kunimoto et al 2004, Jofré Morales et al 2006, Brook 2009.In the present study we found 24 reported cases of attacks by crocodiles on humans in the Yucatan Peninsula, most of them (87.5%) occurring in Quintana Roo and in the city of Cancun, which are the state and city in the peninsula, respectively, most frequented by tourists. Both crocodile species (Crocodylus acutus and C. moreletii) were involved in the attacks and C. moreletii was involved in 2 cases of fatal attacks.…”
supporting
confidence: 52%
“…Bacteria involved in wound infections after crocodilian attacks include Aeromonas hydrophila, Burkholderia pseudomallei, Pseudomonas spp., Serratia spp., Citrobacter diversus, Enterococcus spp., Clostridium spp. and Pantoea agglomerans (Raynor et al 1983, Flandry et al 1989, Mekisic & Wardill 1992 (Murphey et al 1992, Blaylock 1999, Goldstein et al 2002, Kunimoto et al 2004, Jofré Morales et al 2006, Brook 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Among the Pasteurella species, P. multocida is the predominant human pathogen encountered, especially in severe disease cases (235,239), although P. canis may be more prevalent with dog bites (48, [246][247][248]. Common symptoms of pasteurellosis in humans from animal bite wounds are swelling (edema), cellulitis (diffuse, localized inflammation with redness and pain), and bloody or suppurative/ purulent exudate (drainage) at the wound site (39, 41, 48, 49, 160,165,241,[249][250][251][252][253][254][255]. Leukocyte and neutrophil counts are typically high at the infection site, and inflammation develops very rapidly.…”
Section: Pasteurella and Other Pasteurellaceae Diseases In Humans Pasmentioning
confidence: 99%
“…It may appear as cellulitis, abscess, tenosynovitis, septic arthritis and osteomyelitis as well as it may result with rare diseases such as endocarditis, meningitis, cerebral abscess, bacteremia, sepsis and DIC (especially in immunosuppressed patients). Human bites may also cause Hepatitis B, C and HIV infections [4,5] pain, swelling or purulent efflux appears. Such injuries become more complicated by infection until medical treatment.…”
Section: Dear Editor;mentioning
confidence: 99%